Bimetallic‐Based Electrocatalysts for Oxygen Evolution Reaction - Jiang, Jun; Zhou, Xiao‐Li; Lv, Hua‐Gang; Yu, Han‐Qing; Yu, Yan (Advanced functional materials, 2023)
The electrochemical oxygen evolution reaction (OER) is a core electrode reaction for the renewable production of high‐purity hydrogen, carbon‐based fuel, synthetic ammonia, etc. However, the sluggish kinetics of the OER result in a high overpotential and limit the widespread application of OER‐based technologies. Recent studies have shown that bimetallic‐based materials with the synergism of different metal components to regulate the adsorption and dissociation energy of intermediates are promising OER electrocatalyst candidates with a lower cost and energy consumption. In the past two decades, tremendous efforts have been devoted to developing OER applications of bimetallic‐based materials with a focus on compositions, phase, structure, etc., to highlight the synergism of different metal components. However, there is a lack of critical thinking and organized analysis of OER applications with bimetallic‐based materials. This review critically discusses the challenges of developing bimetallic‐based OER materials, summarizes the current optimization strategies to enhance both activity and stability, and highlights the state‐of‐the‐art electrocatalysts for OER. The relationship between the componential/structural features of bimetallic‐based materials and their electrocatalytic properties is presented to form comprehensive electronic and geometric modifications based on thorough analysis of the reported works and discuss future efforts to realize sustainable bimetallic‐based OER applications. The impressive progress in the rational design of bimetals and bimetallic compounds toward oxygen evolution reaction (OER) is summarized. Based on the main advantages and challenges for the bimetallic‐based OER electrocatalysts, the optimization strategies are presented to modify the electronic structure and geometric construction to highlight the synergism characteristics, including compositional regulation, elemental doping, coordination adjustment, interfacial structure establishment, morphology control, and support interaction for achieving efficient OER performance.